Thermoelectric Generator: A Source of Renewable Energy - Fabracuer, Nicanor Jr; Cepe, Reymart; Ricafort, Neil Francis; Rosal, Rhoda Jane (Indonesian Journal of Energy, 2020)
With the natural sources of energy such as fossil fuels is slowly depleting, it became a trend to find new sources of unlimited energy. Renewable source of energy is the best source of unlimited energy for it will be utilizing the resources around like solar, hydro, wind, and many more. One of those newly developed renewable sources utilizes the waste heat developed by individual machines. Since electrical generating machines that use combustion engines generate a considerable amount of waste heat energy from the exhaust gases. Hence, this study focused on waste heat energy harvester by the use of the thermoelectric generator. Thermoelectric power generation is based on a phenomenon called the Seebeck effect. When a temperature difference is established between the hot and cold junctions of two dissimilar materials, a voltage is generated. The heat flow circulation through the semiconductors causes a displacement of charge carriers. A larger delta temperature creates a larger electrical current, ideally, but it is coupled with the fact that a semiconductor is effective only on a temperature range making the thermoelectric generators operational on a limited delta temperature. Primarily, the device was composed of a thermoelectric module mounted on an aluminum plate and placed in an oven. The main objective of the study is to design a circuitry for the thermoelectric generator that aimed to generate a minimum of 20 watts in order to power an AC load. In order to validate the device fabricated, certain measurements needed to be taken during the operation of the prototype. Thus, this device is now a developing source of alternative energy with further studies and innovations for commercial purposes.*The paper has been selected from a collaboration with IPST and 7th ICFCHT 2019 for a conference entitled "Innovation in Polymer Science and Technology (IPST) 2019 in Conjunction with 7th International Conference on Fuel Cell and Hydrogen Technology (ICFCHT 2019) on October 16th - 19th at The Stones Hotel Legian, Bali, Indonesia"